Prospects of Using Aqueous Extracts of Maize, Sorghum and Millet to Lure Alien Invasive Tephritid Fruit Flies in Sudan - Mohamed A.I. Bashir; Abdelgadir M. Abdalla; Faiza M.Abdelmagid; Mohammed E. E. Mahmoud (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
Tephritid Fruit Flies are the most economically important pests attacking fruits and vegetables worldwide reducing and hindered their exportation value. In Sudan, the problem of fruit flies exaggerated after the invasion of the country by the alien invasive species Bactrocera dorsalis in 2005 and B. zonata in 2012. This study focused on developing local food-based attractants to control fruit flies in guava ecosystem in two sites in Gezira State, Sudan. The study revealed the potency of aqueous extracts of sorghum (Sorghum bicolor), millet (Panicum sp) and maize (Zea mays)L to attract both sexes of B.zonata, B. dorsalis and Zeugodacus cucurbitae. The percentage of attracted females represented 70% of the total caught flies. Significant difference was observed at both study sites between different treatments on the number of females (P> F treat=0.0327) and total number of flies of B. zonata (P>F treat=0.0467) per trap per day. In the first site, Trula yeast attracted highest number of B. zonata/trap/day when compared to maize, millet and sorghum respectively, while aqueous extract of Maize was found to be the best among all other attractants in the second site. For B. dorsalis in the first site no significant differences was observed between treatments for females, males and total fruit flies/trap/day while high significant differences were observed between treatments for the caught numbers of males (p>F Treat = 0.0001), females (p>F Treat = 0.0001) and total number of flies/trap/day (p>F Treat = 0.0001) in the second site. Torula yeast attracted more flies of B. dorsalis than all other attractants followed by maize, millet and sorghum respectively. The presence of fruit flies all around the year on the guava ecosystem required non stopping control operations, thus, development of local attractants to reach the optimum levels are highly encouraged to reduce rely on insecticides